Electronic and magnetic properties of NiPd and CoPd nanostructures - Guevara, J. (2010)
We study the dependence of the magnetic properties of NiPd and CoPd segregated nanoclusters and slabs as a function of the 3d magnetic component concentration (x), the chemical order, and size. In the case of clusters we consider 3d cores coated by Pd atoms (3d/Pd) and also onion-like (Pd/3d/Pd) configurations. For the slabs we consider different possible segregated structures of the 3d and 4d atoms and study the evolution of the magnetic properties on these different configurations. We show that Pd coating gives rise to an enhancement of the average magnetic moment of the Ni or Co core atoms and of the Pd atoms as well. Larger values of the average magnetic moments are obtained in the onion-like structures (Pd/3d/Pd) than in the core/shell (3d/Pd) configuration. We compare with theoretical and experimental results available in the literature.